The quest for objectivity: religious pluralism and religious plurality in Malaysia - Ibrahim, Haslina (2015)

(untitled)
There have been many definitions to religious pluralism and religious plurality topped them. In many instances the two terms have been regarded as synonymous and used inter-changeably. This paperwork tries to provide an objective comparison between the two terms grounded on textual and contextual evidences. In depth interviews with several religious leaders in Malaysia have been conducted to further examine the intensity dan the details of the use of the two terms. The comparison is important to shed some light on the conflict arising from the word religious pluralism. In addition, it is hoped that the comparison would bring some clarifications on the origin of religious pluralism and the pregnant meanings it has for the sake of objectivity.